Attachment and Employment Outcomes for People With Spinal Cord Injury: The Intermediary Role of Hope. (January 2017) - Blake, John; Brooks, Jessica; Greenbaum, Hannah; Chan, Fong
The purpose of this article is to evaluate the mediation effect of hope on the relationship between attachment and full-time employment for people with spinal cord injury (SCI). Quantitative descriptive research design using logistic regression, multiple regression, and correlational techniques were used. Eighty-four persons with SCI were recruited from several SCI advocacy organizations in Canada, the United Kingdom, and the United States. The results show that secure attachment, anxious attachment, and hope were significantly related to employment. Hope was found to be a significant mediator of the relationship between attachment and full-time employment. Results provide support for the use of hope-based interventions by vocational rehabilitation counselors working with individuals with SCI.